Project Development Evaluation Towards Construction Waste Management Green Building Concept Oriented - Muhammad Rudiansyah; F Edy Rooslan Santoso; Ronny Durrotun Nasihien (Neutron, 2019)
Surabaya as one of the metropolitan cities in Indonesia, has a high level of project development and an attraction for the community. This is predicted to provide potential changes in environmental quality such as decreased road performance, wastewater and increased volume of waste generation, increased noise and the emergence of community perceptions and concerns about the planned activity. The construction of construction projects will always produce a considerable amount of waste, so that if management is not carried out, the construction waste can become a serious problem for the environment. The waste management model is basically carried out through the stages of avoid, reduce, recycle, and dispoal. This study aims to determine the material that has the greatest potential to produce construction waste. The method used in this study is first to use the Pareto method, the first step that must be done is to rank using Trading Consumable Materials (TCM) based on the total price so that a large price is obtained into the first order, then using the Pareto method to determine the material to be investigated in determining the most construction waste. Furthermore, the second one uses the waste level calculation to determine the waste volume from the results of the Pareto analysis that has been obtained. Furthermore, the third is the calculation of the waste index to determine the volume of residual construction waste in the project in m2 in each day, and the last is the calculation of waste cost to determine whether a large waste volume will produce a large waste as well.